Recovery of energy and plant nutrients from a pharmaceutical organic waste derived from a fermentative biomass: Integration of anaerobic digestion and composting. Issue 3 (June 2017) - Cucina, Mirko; Zadra, Claudia; Marcotullio, Maria Carla; Di Maria, Francesco; Sordi, Simone; Curini, Massimo; Gigliotti, Giovanni
Graphical abstract: Highlights: Energy and plant nutrients are recovered from wastes through biological treatments. A pharmaceutical organic waste was treated by integrated biological systems. Co-digestion of pharmaceutical organic waste produces high bio-methane yields. Composting of the digestate allows to recover plant nutrients. The integrated treatment degrades daptomycin residues efficiently. Abstract: Industrial fermentations for the production of pharmaceuticals generate large volumes of organic wastes which disposal is, nowadays, an environmental and economic issue. In the present paper, the feasibility of energy and plant nutrients recovery from the pharmaceutical organic waste originated from a fermentative biomass used for the daptomycin production was investigated. To achieve this aim, an integrated anaerobic digestion-digestate composting treatment was evaluated, with the purpose of energy (biogas) and organic fertiliser (compost) production. Moreover, the effectiveness of the integrated biological treatment for xenobiotic degradation (e.g. daptomycin) was evaluated. The biomass was initially anaerobically treated to assess its suitability for the production of biogas. The yield in bio-methane obtained when the organic waste was treated in co-digestion with agricultural by-products was 396 Nm 3 tVS −1 . Once optimized the anaerobic digestion process, the produced digestate was composted in a pilot scale apparatus. The composting of the digestate produced an organic amendment rich in macro-nutrients (27.1, 6.2 and 17.8 g kg −1 of total N, P and K, respectively) and compatible with the Italian legislation concerning the production of fertilisers. No traces of daptomycin were detected in the compost, confirming the suitability of the integrated anaerobic-aerobic treatment for the removal of pharmaceuticals. Thus, through the anaerobic-aerobic treatment, it was demonstrated that energy and nutrients may be recovered from an organic waste which disposal, nowadays, is difficult.